Preparation method and application of food-borne cellulose-based nano composite particles
The use of TEMPO-oxidized kelp nanocellulose and sodium caseinate in food-derived nanocomposite particles addresses fucoxanthin's solubility and stability issues, enhancing its therapeutic efficacy by improving encapsulation and activating the Nrf2/HO-1/NQO1 pathway to reduce oxidative stress and lipid accumulation.
Patent Information
- Application Number
- CN202411330092.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-24
AI Technical Summary
Fucoxanthin, a natural compound with therapeutic potential for metabolic diseases, faces challenges due to poor water solubility and light sensitivity, limiting its effective distribution and stability, which are not adequately addressed by traditional cellulose derivatives.
A method for preparing food-derived cellulose-based nanocomposite particles using TEMPO-oxidized kelp nanocellulose as the skeleton structure, combined with sodium caseinate, to stabilize and enhance the encapsulation and bioavailability of fucoxanthin.
The nanocomposite particles improve the structural stability and bioaccessibility of fucoxanthin, effectively reducing oxidative stress and lipid accumulation by activating the Nrf2/HO-1/NQO1 signaling pathway, thereby inhibiting lipid droplet formation and improving metabolic function.
Smart Images

Figure CN119157249A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of precise nutrition delivery, and specifically relates to a preparation method and application of food-derived cellulose-based nanocomposite particles. Background Art
[0002] Metabolic diseases, such as obesity and type 2 diabetes, are often associated with excessive fat accumulation in the body. These conditions are not only due to abnormal lipid metabolism, but are also closely related to oxidative stress, which can further aggravate cellular dysfunction and inflammatory response. In order to simulate the excessive accumulation of fatty acids in the human body and its effects on cell metabolism and function, researchers often use the free fatty acid (FFA) model for in vitro experiments. This model not only helps researchers explore how to regulate fat accumulation by simulating the effects of excess fatty acids on cells in the human body, but is also used to evaluate potential antioxidant therapeutic strategies. Effective antioxidants can reduce oxidative stress and may help restore the normal metabolic function of cells, thereby improving metabolic abnormalities caused by excessive lipid accumulation.
[0003] Fucoxanthin, a natural carotenoid compound extracted mainly from brown algae, has been shown in multiple studies to have potential therapeutic effects on metabolic diseases. This unique marine bioactive substance has significant antioxidant and anti-fat accumulation functions, which can effectively reduce the accumulation of lipids in the body and improve energy metabolism. Fucoxanthin's regulatory effects on blood glucose and cholesterol levels also make it a natural intervention option for the treatment of type 2 diabetes and cardiovascular diseases. These properties make fucoxanthin have broad application prospects in the clinical and functional food fields. Although fucoxanthin has significant biological activity, it faces some limitations in practical applications. One of its main challenges is its extremely poor water solubility, which significantly limits its effective distribution and absorption in the body. In addition, fucoxanthin is sensitive to light and easily degrades under light conditions, which affects its long-term storage stability. These factors together restrict the potential of fucoxanthin as a therapeutic agent, especially in scenarios where long-term or stable administration is required. Therefore, the use of nanotechnology to encapsulate fucoxanthin provides a new solution.
[0004] Cellulose, as a natural polymer material, has been widely used in drug delivery systems in recent years due to its excellent biodegradability and wide sources. For example, carboxymethyl cellulose (CMC) and hydroxypropyl cellulose (HPMC) show good controlled release and stability effects in certain oral controlled release tablets and sustained release injection preparations. However, it should be noted that when dealing with drugs with poor water solubility or easy degradation, these traditional cellulose derivatives may not be able to fully exert their advantages in drug release control and long-term stability. In addition, existing research has mostly focused on non-food-derived materials, which may bring potential safety and biocompatibility issues. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a method for preparing food-derived cellulose-based nanocomposite particles, which uses TEMPO-oxidized kelp nanocellulose as the skeleton structure in the drug delivery system, which can not only stabilize the overall structure of the nanoparticles, but also improve the drug delivery efficiency and bioavailability through its superior physical and chemical properties.
[0006] The present invention provides a method for preparing food-derived cellulose-based nanocomposite particles, comprising the following steps:
[0007] (1) Oxidized food-derived nanocellulose was prepared by 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO)-mediated oxidation using food-derived cellulose as raw material and sodium hypochlorite as oxidant;
[0008] (2) dispersing the oxidized food-derived nanocellulose in water to obtain an oxidized food-derived nanocellulose suspension, and mixing the suspension with a protein aqueous solution to obtain a protein / oxidized food-derived nanocellulose mixture;
[0009] (3) adding the ethanol solution containing the hydrophobic active substance to the protein / oxidized food-derived nanocellulose mixture in step (2), homogenizing, ultrasonicating, and removing the ethanol to obtain food-derived cellulose-based nanocomposite particles.
[0010] In one embodiment of the present invention, in step (1), the food-derived cellulose is nanocellulose or nanofiber crystals from any source.
[0011] In one embodiment of the present invention, in step (1), the food-derived cellulose is kelp nanocellulose, and the preparation method of kelp nanocellulose is: extracting kelp cellulose, then hydrolyzing it with cellulase, and finally obtaining kelp nanocellulose by ultrasonic treatment.
[0012] In one embodiment of the present invention, in step (1), the specific preparation method of oxidized food-derived nanocellulose is: dispersing food-derived cellulose in ultrapure water, and adding TEMPO, NaBr, and NaClO solutions under ice bath conditions; during the reaction, maintaining the pH value in the range of 10±0.2 by using 0.1 mol / L NaOH and HCl; when the pH value of the suspension is constant, adding ethanol to terminate the oxidation reaction; and ultrasonicating, centrifuging, washing, dialyzing, and freeze-drying the suspension.
[0013] In one embodiment of the present invention, in step (1), in the specific preparation method of oxidized food-derived nanocellulose, the addition ratio of food-derived cellulose to ultrapure water is 1:20-2000, g / mL; the addition amounts of TEMPO, NaBr, and NaClO solutions are 0.01-0.08 g, 0.05-0.5 g, and 3-30 mL, respectively.
[0014] In one embodiment of the present invention, in step (2), the protein may be a protein with good water solubility.
[0015] In one embodiment of the present invention, in step (2), the protein is sodium caseinate.
[0016] In one embodiment of the present invention, in step (2), the mass concentration of protein in the protein aqueous solution is 0.25-1%.
[0017] In one embodiment of the present invention, in step (2), the mass concentration of protein and oxidized food-derived nanocellulose in the protein / oxidized food-derived nanocellulose mixture is 0.5-2%; the mass ratio of oxidized food-derived nanocellulose to protein is 1:0.3-3.
[0018] In one embodiment of the present invention, in step (3), the hydrophobic active substance is fucoxanthin.
[0019] In one embodiment of the present invention, in step (3), the concentration of the hydrophobic active substance in the ethanol solution containing the hydrophobic active substance is 1 to 50 mg / mL.
[0020] In one embodiment of the present invention, in step (3), the volume ratio of the ethanol solution containing the hydrophobic active substance to the protein / oxidized food-derived nanocellulose mixture is 1:1-50.
[0021] The present invention provides food-derived cellulose-based nanocomposite particles prepared by the method described above.
[0022] The present invention provides the use of the above-mentioned food-derived cellulose-based nanocomposite particles in the preparation of antioxidant substances for preventing or alleviating free fatty acid-induced oxidative stress-related diseases.
[0023] The present invention also provides the use of the above-mentioned food-derived cellulose-based nanocomposite particles in the preparation of lipid-lowering drugs.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The present invention uses kelp nanocellulose as the skeleton structure of the drug delivery system, which not only increases the overall structural stability of the nanoparticles, but also has lower toxicity to the human body and better environmental friendliness due to its excellent biocompatibility and biodegradability;
[0026] (2) The present invention uses a composite material of kelp nanocellulose and sodium caseinate to effectively improve the encapsulation efficiency of fucoxanthin and its stability during storage;
[0027] (3) The present invention encapsulates fucoxanthin in nanoparticles so that it can be effectively absorbed by cells, significantly improving the bioaccessibility of fucoxanthin, and reducing oxidative stress by activating the Nrf2 / HO-1 / NQO1 signaling pathway, thereby effectively inhibiting lipid droplet formation. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Characterization and analysis of kelp cellulose, kelp nanofiber cellulose and TEMPO-oxidized kelp nanocellulose of Example 1: appearance and TEM image (A), SEM image (B), zeta potential distribution (C) and Fourier transform infrared spectrum (D) of kelp cellulose, kelp nanofiber cellulose and TEMPO-oxidized kelp nanocellulose;
[0029] Figure 2 The encapsulation efficiency of fucoxanthin by TEMPO oxidized kelp nanocellulose / sodium caseinate nanoparticles of Examples 1 to 3 and Comparative Examples 1 to 2 (A) and the retention rate of fucoxanthin after storage for 14 days (B);
[0030] Figure 3 Low temperature cold field scanning electron microscope images of the TEMPO oxidized kelp nanocellulose / sodium caseinate nanoparticles loaded with fucoxanthin of Example 1 and the nanoparticles of Comparative Examples 1 to 2;
[0031] Figure 4 Example 1 Effects of different concentrations of fucoxanthin-loaded kelp nanocellulose / sodium caseinate nanoparticles on cell viability;
[0032] Figure 5 Malondialdehyde (MDA) (A) and glutathione (GSH) (B) levels and superoxide dismutase (SOD) (C) and catalase (CAT) (D) activities in cells of different treatment groups;
[0033] Figure 6Example 1, Comparative Examples 3-4 Nanoparticles alleviate oxidative stress through the Nrf2 / HO-1 / NQO1 signaling pathway: Western blot analysis showed the expression of Nrf2, HO-1 and NQO1 proteins in cells of different treatment groups (A), relative protein expression levels (B), and relative mRNA expression levels of Nrf2 (C), HO-1 (D) and NQO1 (E) in different treatment groups, different letters represent significant differences (p<0.05);
[0034] Figure 7 Example 1, Comparative Examples 3-4 Anti-lipid accumulation ability of nanoparticles in vitro: BODIPY493 / 503 (A) and Oil Red O staining (B) of HepG2 cells; Oil Red O absorbance at 510 nm (C), total cholesterol (TC) (D) and triglyceride (TG) (E) content of cells in different treatment groups, different letters represent significant differences (p<0.05). DETAILED DESCRIPTION
[0035] The crude fucoxanthin (content 70%) used in the following examples and comparative examples was purchased from Shandong Crystal Group. 500 mg of crude fucoxanthin was added to 50 mL of anhydrous ethanol and fully dissolved under light-proof conditions. After complete dissolution, centrifuge at 10,000 rpm for 15 min to remove insoluble impurities. Subsequently, the supernatant containing fucoxanthin was taken and diluted to a concentration of 5 mg / mL for the preparation of nanoparticles loaded with fucoxanthin.
[0036] The preparation of kelp nanocellulose mentioned in the examples is prepared by the following method: the washed kelp is placed in a 60°C oven until it is completely dried, the dried kelp is taken out and ground into powder, 20g of the powder is accurately weighed and dispersed in 1L of 2wt% sodium hydroxide aqueous solution, reacted at 120°C for 2h, centrifuged, and the precipitate is thoroughly washed. This step is repeated 2-3 times to remove hemicellulose, and the precipitate is further dispersed in 1L of aqueous solution containing 3.5wt% NaOH, 150mL glacial acetic acid, and 16g NaClO, bleached at 80°C for 1h, centrifuged to collect the precipitate and thoroughly washed, and this step is repeated 2-3 times until the precipitate appears white. The precipitate is suspended in 1L of aqueous solution containing 2wt% NaOH, 0.8wt% Na3PO4·12H2O and 0.8wt% Na2SiO3·9H2O, reacted at 100°C for 2h to remove lignin, centrifuged and washed the precipitate until the pH is neutral, and kelp cellulose (KC) is collected by freeze drying. Accurately weigh 0.5 g of kelp cellulose, disperse it in 250 ml of deionized water, add 50 mg of cellulase, and react for 3 hours at 60°C and pH = 4.8. After the reaction, centrifuge at 10000 rpm for 10 minutes to remove excess cellulase, ultrasonicate with an ultrasonic cell disruptor for 10 minutes at 450 W, and freeze-dry to collect kelp nanocellulose (KNC).
[0037] In the following description of the embodiments, wt% refers to mass percentage, for example, "1 wt% sodium caseinate" means that 100 g of deionized water contains 1 g of sodium caseinate.
[0038] The measurement methods involved in the following embodiments are:
[0039] (I): Characterization and analysis methods of kelp nanocellulose: The appearance of the cellulose suspension was photographed by a camera, and the microscopic morphology of cellulose was observed using a transmission electron microscope (TEM, JEM-2100UHR, Japan) and a field emission scanning electron microscope (FE-SEM, SM-7800F, Japan); the Zeta potential of cellulose was measured by a Malvern particle size potential meter (ZETASIZER 3000HSA, UK) at 25°C, and the sample concentration was 1 mg / mL; the functional groups of the samples were determined using a Fourier transform infrared spectrometer (FT-IR, Spectrum Two, USA), and the measurement range of these spectra was from 4000 cm -1 Up to 400cm -1 , resolution 4cm -1 .
[0040] (II): Determination of the encapsulation rate and retention rate of fucoxanthin: 0.5 mL of sample was mixed with 2 mL of a mixed solution of dichloromethane / methanol (volume ratio 2:1), vortexed thoroughly, and centrifuged at 8000 rpm for 10 min. The dichloromethane layer was collected, and the absorbance at 450 nm was measured. The standard curve y = 0.1092x-0.011 (R 2 =0.9995) to calculate the content of Fx. The encapsulation efficiency (EE) and retention rate of Fx were calculated using the following equation:
[0041]
[0042] (III): Observation of the microscopic morphology of fucoxanthin-loaded nanoparticles: The microstructure of the nanoparticles was observed by cryo-transmission scanning electron microscopy (Cryo-SEM, Hitachi, Japan); 10 μL of the sample was rapidly frozen by liquid nitrogen and then gold-sprayed to enhance the conductivity and image clarity of electron microscopy imaging; after gold-spraying, the sample was transferred to a cryo-transmission scanning electron microscope for observation.
[0043] (IV): Method for determining the biocompatibility of nanoparticles: First, a sample solution loaded with Fx nanoparticles (concentrations of 0, 21, 42, 84, 126, 168, and 210 μg / mL) was prepared using DMEM medium. 100 μl of HepG2 cell suspension was plated at 5×10 cells per well. 3 The cells were seeded in a 96-well microplate at a density of 100 μl and incubated at 37°C and 5% CO2 for 24 h. The culture medium in the well plate was then replaced with 100 μl of sample solution and incubated for another 24 h. Next, 20 μl of 5 mg / mL 3-(4,5)-dimethylthiazol(-z-y1)-3,5-di-phenytetrazoliumromide (MTT, Beyotime Biotechnology, ST1537-1 g) was added to each 96-well plate and further incubated at 37°C for 4 h. After removing the culture medium, 150 μl of DMSO was added to each well, and finally the absorbance of the 96-well plate at a wavelength of 570 nm was measured and the cell viability was calculated.
[0044] (V): Determination of the antioxidant capacity of nanoparticles: DMSO stock solutions of 78 mM and 354 mM palmitic acid (PA) and oleic acid (OA) were prepared, and then the palmitic acid and oleic acid stock solutions were mixed in DMEM culture medium at a molar ratio of 1:2 to make the final free fatty acid concentration 1 mM. HepG2 cells were cultured at 1×10 5The cells were seeded in a 12-well microplate at a density of 10 cells and incubated at 37°C and 5% CO2 for 24 hours. The culture medium in the well plate was then replaced with 1 mL of DMEM culture medium containing the sample (the concentration of the nanoparticles loaded with fucoxanthin was 42 μg / mL, equivalent to 2 μg / mL free fucoxanthin) and cultured for 12 hours. After 12 hours, the culture medium containing the sample was removed, and DMEM culture medium containing free fatty acids and samples was added and incubated for 24 hours. The control group was treated with fresh culture medium only, and the model group was stimulated with free fatty acids only. The levels of glutathione (GSH), total superoxide dismutase (SOD), catalase (CAT), and malondialdehyde (MDA) in the cells were determined using biochemical kits provided by Nanjing Jiancheng Bioengineering Research Institute.
[0045] (Six): Protein immunoblotting assay method: According to the method for determining the antioxidant capacity of nanoparticles, cells were first treated, collected and lysed, and proteins were separated by SDS-PAGE and transferred to PVDF membranes. After blocking with 5% skim milk solution for 2 hours, the membranes were washed three times with Tris-HCl buffer solution containing 0.05% Tween 20. Finally, the corresponding antibodies were used, and the protein bands were visualized using enhanced chemiluminescence reagents. Protein expression was quantitatively analyzed by using ImageJ software. Detailed antibody information is as follows: Nrf2 (A0674, ABclonal, 1:1000), HO-1 (A1346, ABclonal, 1:1000), NQO1 (A23486, ABclonal, 1:1000), β-actin (AC038, ABclonal, 1:60000).
[0046] (VII): Real-time quantitative PCR assay method: First, total RNA was extracted from HepG2 cells using Trizol. Subsequently, RNA was reverse transcribed into cDNA using the Evo M-MLV RT kit and gDNA Clean for qPCRⅡ. The RT-PCR analysis cycle conditions were as follows: initial denaturation at 95°C for 30 seconds, followed by 45 cycles, each cycle consisting of 95°C for 5 seconds and 60°C for 30 seconds. The final extension phase was 95°C for 15 seconds, followed by 60°C for 15 seconds. The relative mRNA level was measured by 2 -ΔΔCtThe primer pairs were: 5′-TCAAGAAAGGGTGTAACGCAACTA-3′ and 5′-CGACAGGATGCAGAAGGAGAT-3′ of human β-actin, 5′-TACTCCCAGGTTGCCCACA-3′ and 5′-CATCTACAAACGGGAATGTCTGC-3′ of human Nrf2, 5′-CGGGCCAGCAACAAAGTG-3′ and 5′-AGTGTAAGGACCCATCGGAGAA-3′ of human HO-1, and 5′-GGGCAAGTCCATCCCAACTG-3′ and 5′-GCAAGTCAGGGAAGCCTGGA-3′ of human NQO1.
[0047] (VIII): Determination of the anti-lipid accumulation ability of nanoparticles in vitro: The cells were treated as described in the method for determining the antioxidant capacity of nanoparticles, and the anti-fat accumulation ability of the nanoparticles was visualized using an Oil Red O staining kit and a lipid droplet green fluorescence detection kit (BODIPY493 / 503). The total cholesterol (TC) and triglyceride (TG) levels of the cells were then detected using a kit provided by Nanjing Jiancheng Bioengineering Institute.
[0048] Example 1
[0049] S1: 1g of kelp nanocellulose was dispersed in 500mL of ultrapure water, and 0.016g of TEMPO, 0.1g of NaBr and 7.2mL of NaClO solution were added under ice bath conditions. During the reaction, the pH value was maintained in the range of 10±0.2 by using 0.1mol / L of NaOH and HCl. When the pH value of the suspension was constant, the oxidation reaction was considered to be completed, and 3ml of ethanol was added to terminate the oxidation reaction. The suspension was ultrasonically treated at 400W for 5 minutes, and finally centrifuged at 10,000 rpm for 15 minutes. The precipitate was washed with deionized water several times and then dialyzed, and freeze-dried to obtain oxidized kelp nanocellulose (TKNC);
[0050] S2: at 4°C, 1 g of sodium caseinate was dissolved in 100 mL of deionized water, and oxidized kelp nanocellulose was dispersed in deionized water to obtain an oxidized kelp nanocellulose suspension with a concentration of 10 mg / mL. The two solutions were mixed and homogenized at 8000 rpm for 30 s to form a uniform mixture to obtain a sodium caseinate / oxidized kelp nanocellulose mixture, the concentration of the total biopolymer was set to 1 wt% (i.e., the mass concentration of protein and oxidized food-derived nanocellulose in the protein / oxidized food-derived nanocellulose mixture was 1%), and the mass ratio of oxidized kelp nanocellulose to sodium caseinate was 1:3;
[0051] S3: 1 mL of fucoxanthin ethanol solution (5 mg / mL) was added dropwise into the mixture of 10 mL of S2 and homogenized at 10000 rpm for 2 min to form a crude emulsion;
[0052] S4: The crude emulsion was sonicated at 600 W for 10 min in an ice bath, and then the ethanol was evaporated to obtain the fucoxanthin-loaded nanoparticles (P3C1@Fx).
[0053] In the present invention, TEMPO-oxidized kelp nanocellulose (TKNC) was successfully prepared by TEMPO oxidation, and a detailed comparative analysis was conducted between it and kelp cellulose (KC) without enzymatic hydrolysis and ultrasonic treatment and kelp nanocellulose (KNC) without oxidation treatment. The comprehensive characterization of these nanocelluloses can not only reveal their microstructure and chemical properties, but also evaluate their application potential as potential drug carrier materials. Figure 1 As shown in Figure A, larger fiber bundles of KC were observed under TEM. These fiber bundles were intact in structure without any surface modification, showing a natural fiber state, while the fibers of the KNC sample were more dispersed and smaller in size, indicating that enzymatic hydrolysis and ultrasonic treatment effectively decomposed the fiber bundles and released smaller fibers. In contrast, TKNC not only showed higher dispersibility, but also formed fine and uniform nanofibers. Such highly dispersed nanofibers can provide a larger surface area, help enhance the stability of the suspension, and may be beneficial for subsequent functionalization or drug adsorption processes. The surface microstructure of kelp cellulose of different samples was further observed by SEM, and the significant differences showed that the treatment method had a significant effect on the cellulose structure ( Figure 1 B). First, the fiber structure of the KC sample is relatively rough and highly aggregated, which reflects the characteristics of incomplete decomposition of the fiber bundles. Compared with the KC sample, the KNC sample showed a more open structure and significantly increased pores after enzymatic hydrolysis and ultrasonic treatment. Finally, the TKNC sample was further treated with TEMPO oxidation to present a highly porous and mesh structure, which not only increased the specific surface area of the material, but also provided more space for drug loading. At the same time, this structure can effectively enhance the ability of material exchange. These characteristics make TKNC an ideal drug carrier material. Zeta potential is an important parameter for evaluating the stability of suspended particles. The Zeta potential of the KC sample is -5.24±1.31mV. This low negative value indicates that the fiber surface charge is small, resulting in insufficient repulsion between particles, resulting in low stability of the suspension. After enzymatic hydrolysis, ultrasonic treatment and TEMPO oxidation treatment, the potential of cellulose dropped significantly to -29.34±1.83mV. This is because the TEMPO oxidation process increases the carboxyl content on the fiber surface, thereby significantly increasing the surface negative charge ( Figure 1C). These additional negative charges enhance the electrostatic repulsion between fibers, which in turn enhances the stability of the suspension and the dispersibility of the cellulose. FTIR spectroscopy provides insight into the changes in the chemical structure of the different treated samples of kelp cellulose. Figure 1 As shown in D, all samples have a peak at 3354 cm -1 The hydroxyl (OH) stretching vibration peak near 2917 cm -1 The CH stretching vibration peaks near 904 cm-1 were all retained, indicating that the basic structure of cellulose remained stable during the treatment process, and the hydrogen bonding between water molecules and hydroxyl groups and the structure of saturated fatty carbon chains did not change significantly. -1 The characteristic peak of glucose β-glycosidic bond in cellulose was observed near 1605 cm-1, which was retained in all samples, indicating that the sugar ring structure of cellulose was not destroyed. -1 The peak at 1734 cm-1 of the TKNC sample was enhanced, which is usually associated with the absorption of cellulose-bound water, indicating that enzymatic hydrolysis and ultrasonic treatment may have increased the hydration capacity of cellulose. -1 There is an obvious carboxyl (C=O) stretching vibration peak at , which is introduced by TEMPO oxidation treatment. The appearance of this peak proves that the carboxyl content on the cellulose surface is increased by TEMPO treatment, which has a positive effect on the solubility of the fiber.
[0054] Comparative Example 1
[0055] Preparation method of kelp nanofiber nanoparticles P0C1@Fx loaded with fucoxanthin:
[0056] S1: 1g of kelp nanocellulose was dispersed in 500mL of ultrapure water, and 0.016g of TEMPO, 0.1g of NaBr and 7.2mL of NaClO solution were added under ice bath conditions; during the reaction, the pH value was maintained in the range of 10±0.2 by using 0.1mol / L of NaOH and HCl. When the pH value of the suspension was constant, the oxidation reaction was considered to be completed; the oxidation reaction was terminated by adding 3ml of ethanol; the suspension was ultrasonically treated at 400W for 5 minutes, and finally centrifuged at 10,000 rpm for 15 minutes. The precipitate was washed with deionized water several times and then dialyzed. The oxidized kelp nanocellulose was obtained after freeze drying;
[0057] S2: Oxidized kelp nanocellulose (concentration of 10 mg / mL) was suspended in deionized water at 4 °C;
[0058] S3: 1 mL of fucoxanthin ethanol solution (5 mg / mL) was added dropwise into 10 mL of oxidized kelp nanocellulose in S2 and homogenized at 10000 rpm for 2 min to form a crude emulsion;
[0059] S4: The crude emulsion was sonicated at 600 W in an ice bath for 10 min, and then the ethanol was evaporated to obtain the fucoxanthin-loaded nanoparticles (POC1@Fx).
[0060] Comparative Example 2
[0061] Preparation method of sodium caseinate nanoparticles loaded with fucoxanthin (P1C0@Fx):
[0062] S1: Dissolve 1 g sodium caseinate in 100 mL deionized water at 4 °C.
[0063] S2: 1 mL of fucoxanthin ethanol solution (5 mg / mL) was added dropwise into 10 mL of sodium caseinate solution of S1 and homogenized at 10000 rpm for 2 min to form a crude emulsion;
[0064] S3: The crude emulsion was sonicated at 600 W for 10 min in an ice bath, and then the ethanol was evaporated to obtain the fucoxanthin-loaded nanoparticles (P1C0@Fx).
[0065] Example 2
[0066] The preparation method was consistent with that of Example 1, except that the concentration of the total biopolymer was set to 1 wt %, the mass ratio of oxidized kelp nanocellulose to sodium caseinate was 1:1, and fucoxanthin-loaded nanoparticles (P1C1@Fx) were obtained.
[0067] Example 3
[0068] The preparation method was consistent with that of Example 1, except that the concentration of the total biopolymer was set to 1 wt %, the mass ratio of oxidized kelp nanocellulose to sodium caseinate was 3:1, and fucoxanthin-loaded nanoparticles (P1C3@Fx) were obtained.
[0069] Comparative Example 3
[0070] Free fucoxanthin: Free fucoxanthin was directly dispersed in ultrapure water to obtain a fucoxanthin solution with a concentration of 5 mg / mL.
[0071] like Figure 2As shown in Figure A, compared with the use of cellulose (P0C1@Fx comparative example 1) or protein (P1C0@Fx comparative example 2) alone, the sample of Example 1 (P3C1@Fx) showed significant advantages in improving the encapsulation rate of Fx. The encapsulation efficiency of P3C1@Fx reached 82.2±0.87%, the encapsulation efficiency of P1C3@Fx was 67.87±1.96%, and the encapsulation efficiency of P1C1@Fx was 78.82±1.59%. This shows that the composite structure of cellulose and protein plays a key role in improving the encapsulation efficiency. The higher protein to cellulose ratio in P3C1@Fx may increase the internal structural complexity of the composite material. In this complex microstructure, more micropores and potential binding sites may be formed, which provide more physical encapsulation space and chemical adsorption points for Fx. In addition, the intermolecular forces that may exist between cellulose and protein may also enhance the stability of Fx in the composite, thereby effectively preventing the loss during the processing process.
[0072] In order to further explore the stability of fucoxanthin-loaded nanoparticles under actual storage conditions, a 14-day storage experiment was conducted on these nanoparticles. Figure 2 As shown in Figure B, the retention rate of fucoxanthin after 14 days was measured, and the retention rate of fucoxanthin loaded in the nanoparticles of Example 1 reached 56.12±1.89%, which was significantly higher than the retention rate of fucoxanthin in Comparative Example 1 (33.93±1.15%) and the retention rate of fucoxanthin in Comparative Example 2 (42.92±0.15%). In addition, the retention rate of fucoxanthin in Example 2 was 50.43±2.12%, the retention rate of fucoxanthin in Example 3 was 42.05±0.77%, and the retention rate of free fucoxanthin in Comparative Example 3 was 22.12±0.51%. The highest retention rate in the sample of Example 1 can be attributed to its higher sodium caseinate content, which not only improves the initial encapsulation efficiency, but also enhances the structural stability of the nanoparticles through the synergistic effect of protein and cellulose. As a natural polymer with high dispersibility and porosity, TKNC can provide additional protection for fucoxanthin and reduce the risk of mechanical or chemical degradation of fucoxanthin.
[0073] Cryo-SEM images provide a detailed view of the microstructure of the nanoparticles ( Figure 3). When cellulose exists alone (Comparative Example 1), the microscopic image reveals a relatively regular and continuous network structure with obvious and evenly distributed pores. This shows that cellulose can form a stable scaffold structure. In the pure protein group (Comparative Example 2), the image reveals obvious aggregation of particles. In the absence of cellulose, it is difficult for particles to form a stable network structure and they are prone to aggregation, which may affect their application effect in drug delivery systems. When the two are combined (Example 1), it is observed that cellulose effectively prevents excessive aggregation of particles and ensures uniform distribution of particles on a microscopic scale. In short, the addition of food-derived nanocellulose significantly affects the stability and encapsulation efficiency of nanoparticles, and its synergistic effect with protein enhances the overall performance of nanoparticles.
[0074] Comparative Example 4
[0075] Preparation method of unloaded fucoxanthin nanoparticles P3C1:
[0076] S1: 1g of kelp nanocellulose was dispersed in 500mL of ultrapure water, and 0.016g of TEMPO, 0.1g of NaBr and 7.2mL of NaClO solution were added under ice bath conditions; during the reaction, the pH value was maintained in the range of 10±0.2 by using 0.1mol / L of NaOH and HCl. When the pH value of the suspension was constant, the oxidation reaction was considered to be completed; the oxidation reaction was terminated by adding 3ml of ethanol; the suspension was ultrasonically treated at 400W for 5 minutes, and finally centrifuged at 10,000 rpm for 15 minutes. The precipitate was washed with deionized water several times and then dialyzed. The oxidized kelp nanocellulose was obtained after freeze drying;
[0077] S2: At 4 °C, 1 g of sodium caseinate was dissolved in 100 mL of deionized water, and oxidized kelp nanocellulose (concentration of 10 mg / mL) was resuspended in deionized water. The two solutions were mixed and homogenized at 8000 rpm for 30 s to form a uniform mixture. The concentration of the total biopolymer was set to 1 wt %, and the mass ratio of oxidized kelp nanocellulose to sodium caseinate was 1:3.
[0078] S3: 1 mL of ethanol solution was added dropwise into the mixture of 10 mL of S3 and homogenized at 10000 rpm for 2 min to form a crude emulsion;
[0079] S4: Nanoparticles without fucoxanthin loading (P3C1) were obtained by sonicating the crude emulsion at 600 W for 10 min in an ice bath, followed by rotary evaporation of ethanol.
[0080] The safety of the nanoparticle material was verified by the MTT results. Figure 4), even at a higher sample concentration (P3C1@Fx concentration of 210 μg / mL), the cell viability remained above 93%. In summary, the nanoparticles demonstrated extremely high biosafety and cell compatibility, which is particularly critical in the field of drug delivery.
[0081] In order to further explore the response of cells in the face of oxidative stress, the effectiveness of the cellular antioxidant defense system was evaluated and revealed by measuring key biochemical indicators. These indicators include the level of lipid peroxides (represented by malondialdehyde MDA), the content of intracellular antioxidant glutathione (GSH), and antioxidant enzyme activities such as superoxide dismutase (SOD) and catalase (CAT). These measurements can not only reflect the stress state of cells under oxidative stress, but also reveal the effectiveness of antioxidant interventions. MDA is the main product of cell membrane lipid peroxidation and is widely used as an indicator to assess the degree of oxidative damage to cells. In this patent, the model group (OA+PA) treatment significantly increased the MDA content, indicating that the cells suffered severe oxidative stress. In contrast, after P3C1@Fx treatment, the cellular MDA content was significantly reduced, and its level was not significantly different from that of the control group, indicating that P3C1@Fx treatment not only significantly inhibited lipid peroxidation, but also its effect was sufficient to restore oxidative damage to almost normal levels ( Figure 5 A). In further biochemical analysis, the activities of GSH, SOD, and CAT, which are key antioxidant defense indicators in cells, were evaluated simultaneously. The results showed that P3C1@Fx treatment significantly restored the content of GSH, indicating that it effectively maintained the reducing environment of cells and alleviated oxidative stress ( Figure 5 B). Similarly, the activities of SOD and CAT also showed significant increases in the P3C1@Fx treated group ( Figure 5 C, 5D), the synergistic effect of SOD and CAT further enhanced the cell's ability to scavenge free radicals and effectively prevented cell damage caused by oxidative stress. These results together demonstrate the high efficiency of P3C1@Fx in enhancing the antioxidant defense capacity of cells and demonstrate its potential application value in preventing and alleviating free fatty acid-induced oxidative stress-related diseases.
[0082] In order to gain a deeper understanding of how the nanoparticle P3C1@Fx (Example 1) enhances the antioxidant capacity of cells through molecular mechanisms, this study focused on its activation effect on the Nrf2 signaling pathway. Western blot and RT-PCR techniques were used to evaluate the expression changes of Nrf2 and its downstream antioxidant response elements, such as HO-1 and NQO1, under free fatty acid-induced oxidative stress conditions. Nrf2 is a key transcription factor that regulates cellular antioxidant responses, and its activation can promote the expression of a series of defensive genes, thereby enhancing the antioxidant capacity and survival rate of cells. This patent aims to reveal how P3C1@Fx regulates the Nrf2 pathway by quantifying the expression of these key proteins and genes, thereby providing an effective antioxidant strategy. Figure 6 A and 6B show the expression of Nrf2, HO-1, and NQO1 proteins. Under oxidative stress conditions, the expression of Nrf2 was downregulated, probably because oxidative stress exceeded the cell's ability to self-regulate. In contrast, P3C1@Fx treatment significantly upregulated the expression of Nrf2, indicating that the nanoparticles enhanced its antioxidant response by stabilizing and activating Nrf2. HO-1, as a downstream target protein of Nrf2, also had its expression significantly increased in P3C1@Fx treatment. HO-1 is a stress protein with powerful antioxidant and anti-inflammatory effects, which can help cells alleviate damage caused by free radicals. Therefore, the activation of Nrf2 directly promoted the increased expression of HO-1, further enhancing the cell's protective mechanism. Similarly, NQO1, as another downstream target protein of Nrf2, was also significantly upregulated in P3C1@Fx treatment. Further RT-PCR results confirmed that the expression of Nrf2 and its downstream proteins HO-1 and NQO1 mRNA was consistent with the protein expression results. After P3C1@Fx treatment, compared with the model group (OA+PA group), the expression levels of Nrf2, HO-1, and NQO1 mRNA were significantly enhanced, increasing by 1.876±0.125 times, 1.710±0.190 times, and 2.014±0.230 times, respectively ( Figure 6 C, 6D, 6E). These results jointly verified the antioxidant effect of the P3C1@Fx group of Example 1 at the molecular level, which was significantly better than the free fucoxanthin of Comparative Example 3 and the unloaded fucoxanthin nanoparticle group of Comparative Example 4, revealing that it enhances the cell protection mechanism by enhancing Nrf2 and its regulated antioxidant response pathway.
[0083] The ability of this nanocarrier to enhance Fx's ability to inhibit lipid droplet accumulation was evaluated in a HepG2 cell model. The effects of Example 1 on lipid droplet accumulation were visually compared with Comparative Examples 3 and 4 by using Oil Red O and BODIPY 493 / 503 fluorescent staining techniques, thereby verifying the potential advantages of nanotechnology in enhancing its biological activity. BODIPY 493 / 503 is used as a fluorescent probe to label neutral fats in cells. The dye has very weak fluorescence in water and other polar solvents, but once combined with triglycerides, it will emit bright green fluorescence. Figure 7 As shown in A, the experiment successfully established a lipid accumulation model induced by excessive free fatty acids. The cells in the OA+PA group showed a significant increase in lipid droplets compared to the control group, which was visible through the strong green fluorescence of the BODIPY 493 / 503 fluorescent probe. Based on this model, the effects of each treatment group were compared and analyzed. The green fluorescence intensity of the comparative example 4 group did not show significant differences compared with the model group, indicating that pure P3C1 has limited effect on inhibiting lipid accumulation. This may be because the nanoshell material itself lacks a direct regulatory effect on the lipid metabolism process. In contrast, free Fx (Comparative Example 3) showed a certain lipid droplet reduction effect, which is consistent with its known anti-fat activity. However, when P3C1 was successfully loaded with Fx (P3C1@Fx, Example 1), it showed the most significant reduction in lipid droplets, indicating that the nanoparticles improved the intracellular delivery efficiency of Fx and its bioaccessibility, thereby enhancing its anti-fat accumulation effect. The results of Oil Red O staining also support this observation ( Figure 7 B), in order to quantitatively analyze the results of Oil Red O staining, the stained Oil Red O was extracted with isopropanol and the absorbance was measured by a spectrophotometer. Figure 7 As shown in Figure C, the P3C1@Fx group showed a lower absorbance (1.220±0.021) than the free Fx and P3C1 groups, confirming its superiority in inhibiting fat accumulation. The effects of each treatment group were further analyzed and discussed by measuring the triglyceride (TG) and total cholesterol (TC) contents in the cells ( Figure 7D, 7E). The TG and TC contents of the OA+PA group were significantly higher than those of the control group, which is consistent with the expected effect of inducing lipid accumulation by adding free fatty acids. Compared with other treatment groups, the TG and TC contents of the P3C1@Fx group were the lowest, 0.366±0.011 and 1.021±0.028mmol / gprot, respectively. Overall, by loading the hydrophobic active substance fucoxanthin into P3C1, its ability to inhibit fat accumulation in the HepG2 cell model can be significantly improved. This finding was not only verified by the visualized lipid droplet accumulation, but also further supported by the determination of TG and TC. The significant reduction in lipid droplets and the significant reduction in TG and TC contents shown in the P3C1@Fx group highlight the potential of nanotechnology in improving the bioaccessibility of active ingredients and their efficacy. These results provide a strong experimental basis for the use of nanocarriers to enhance the application of marine carotenoids in anti-obesity therapy, especially in the inhibition of lipid droplet formation.
[0084] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing food-derived cellulose-based nanocomposite particles, characterized in that: The following steps are involved: (1) Oxidized food-derived nanocellulose was prepared by using food-derived cellulose as raw material and sodium hypochlorite as oxidant via a 2,2,6,6-tetramethylpiperidin-1-oxyl-mediated oxidation method; (2) dispersing the oxidized food-derived nanocellulose in water to obtain an oxidized food-derived nanocellulose suspension, and mixing the suspension with a protein aqueous solution to obtain a protein / oxidized food-derived nanocellulose mixture; (3) adding the ethanol solution containing the hydrophobic active substance to the protein / oxidized food-derived nanocellulose mixture in step (2), homogenizing, and removing the ethanol to obtain food-derived cellulose-based nanocomposite particles.
2. The method for preparing food-derived cellulose-based nanocomposite particles according to claim 1, characterized in that: In step (1), the food-derived cellulose is nanocellulose or nanofiber crystals from any source.
3. The method for preparing food-derived cellulose-based nanocomposite particles according to claim 1, characterized in that: The food-derived cellulose is kelp nanocellulose. The preparation method of kelp nanocellulose is: extract kelp cellulose, then hydrolyze it with cellulase, and finally obtain kelp nanocellulose through ultrasonic treatment.
4. The method for preparing food-derived cellulose-based nanocomposite particles according to claim 1, characterized in that: In step (1), the specific preparation method of oxidized food-borne nanocellulose is: dispersing food-borne cellulose in ultrapure water, and adding 2,2,6,6-tetramethylpiperidine-1-oxyl, NaBr, and NaClO solutions under ice bath conditions; during the reaction, maintaining the pH value in the range of 10±0.2 by using 0.1 mol / L NaOH and HCl; when the pH value of the suspension is constant, adding ethanol to terminate the oxidation reaction, followed by sonication, centrifugation, washing, dialysis, and freeze-drying to obtain the oxidized food-borne nanocellulose.
5. The method for preparing food-derived cellulose-based nanocomposite particles according to claim 1, characterized in that: In step (2), the protein is a protein with good water solubility; the mass concentration of the protein in the protein aqueous solution is 0.25-1%.
6. The method for preparing food-derived cellulose-based nanocomposite particles according to claim 1, characterized in that: In step (2), the mass concentration of protein and oxidized food-derived nanocellulose in the protein / oxidized food-derived nanocellulose mixture is 0.5-2%; the mass ratio of oxidized food-derived nanocellulose to protein is 1:0.3-3.
7. The method for preparing food-derived cellulose-based nanocomposite particles according to claim 1, characterized in that: In step (3), the hydrophobic active substance is fucoxanthin; in the ethanol solution containing the hydrophobic active substance, the concentration of the hydrophobic active substance is 1 to 50 mg / mL; and the volume ratio of the ethanol solution containing the hydrophobic active substance to the protein / oxidized food-derived nanocellulose mixture is 1:1 to 50.
8. Food-derived cellulose-based nanocomposite particles prepared by the method according to any one of claims 1 to 7.
9. Use of the food-derived cellulose-based nanocomposite particles according to claim 8 in the preparation of antioxidant substances for preventing or alleviating free fatty acid-induced oxidative stress-related diseases.
10. Use of the food-derived cellulose-based nanocomposite particles according to claim 8 in the preparation of lipid-lowering drugs.
Citation Information
Patent Citations
Preparation method of oxidized nano-cellulose / collagen composite sponge
CN105079886A
Method for improving sedimentation resistance and thermal stability of celery seed nanocellulose
CN113995121A
Preparation method of nanocellulose modified fucoxanthine-loaded liposome
CN117695407A
PH response type fish gelatin-chondroitin sulfate nano-particles for loading fucoxanthin and preparation method of pH response type fish gelatin-chondroitin sulfate nano-particles
CN118266578A
